Impact of changes in the WHO's 2019 update of DDDs on the measurement of adult hospital antibacterial consumption in Catalonia (Spain), 2008–18. Issue 4 (16th October 2020) - Grau, Santiago; Hernández, Sergi; Limón, Enric; Calbo, Esther; Horcajada, Juan P; ,
Abstract: Objectives: In 2019 the WHO fully adopted new DDD values. The objective of this study is to analyse their impact on the measurement of consumption of antibacterials in hospitals participating in the Catalan Infection Control and Antimicrobial Stewardship National Program (VINCat-PROA) in Catalonia (Spain) between 2008 and 2018. Methods: The anatomical therapeutic chemical/DDD system was used to monitor adult hospital antibacterial consumption expressed in DDD/100 bed-days. Consumption from 2008 to 2018 was calculated using both pre- and post-update DDD values. Differences were calculated as the percentage variation in DDD/100 bed-days and analysed with Student's t -test. Simple linear regressions were performed to evaluate the trends in adult antimicrobial consumption over the study period. Results: The overall consumption according to post-update DDD values decreased by 12.2% ( P < 0.001) compared with the pre-update DDD values. Penicillins (−19.6.%; P < 0.001) and carbapenems (−19.0%; P = 0.023) showed the greatest reduction, followed by cephalosporins (−7.7%; P = 0.021) and quinolone antibacterials (−7.7%; P = 0.017). ICU services showed the greatest overall reduction (−13.1%; P < 0.001). From 2008 to 2018 there was a statistically significant decrease in consumption of penicillins and quinolone antibacterials and a statistically significant increase in cephalosporin and carbapenem consumption with both pre- and post-update DDD values. There were no variations in the ranking of consumption between the pre- and post-update DDD values. Conclusions: The WHO's updates of DDDs have had a significant impact on the measurement of antibacterial consumption. In our region, they have corrected an overestimation of penicillin and carbapenem consumption amounting to 19%. It is essential to bear these findings in mind for an accurate assessment of temporal trends and benchmarking.